2017
DOI: 10.3892/mmr.2017.8084
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Astragalus polysaccharides in attenuating insulin resistance in Rats with type 2 diabetes mellitus via the regulation of liver microRNA‑203a‑3p

Abstract: Insulin resistance (IR) is a common feature of type 2 diabetes mellitus (T2DM). Astragalus polysaccharides (APS) is a natural medicine that is used to treat T2DM. However, the mechanism by which APS regulates micro (mi)RNA in the treatment of IR has not been investigated. The purpose of the present study was to investigate differential miRNA expression between normal, T2DM model and APS treatment rats, as well as changes in miRNA and its downstream gene expression levels after APS treatment in T2DM Goto Kakiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Taken together with the observation that miR-204 directly binded to SIRT1 3 UTR to negatively regulate expression of SIRT1, our data suggested that APS exerted potent regulatory effect on miR-204/SIRT1 axis in RPE cells. In previous study, APS attenuated insulin resistance through regulating miR-203a-3p in Type 2 diabetic mellitus [23]. In addition, APS treatment regulated SIRT1 pathway to improve insulin resistance [24] and ameliorate mitochondria dysfunction [25].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Taken together with the observation that miR-204 directly binded to SIRT1 3 UTR to negatively regulate expression of SIRT1, our data suggested that APS exerted potent regulatory effect on miR-204/SIRT1 axis in RPE cells. In previous study, APS attenuated insulin resistance through regulating miR-203a-3p in Type 2 diabetic mellitus [23]. In addition, APS treatment regulated SIRT1 pathway to improve insulin resistance [24] and ameliorate mitochondria dysfunction [25].…”
Section: Discussionmentioning
confidence: 84%
“…ceRNA sponges therefore represent an alternative mechanism of miR-204 regulation. Accumulating reports have highlighted the roles of APS in regulating miRNA expression, for example, APS up-regulated or maintained the miR-203a-3p expression levels to attenuate insulin resistance of Type 2 diabetes mellitus [23]. APS suppressed miR-721 expression to attenuate TNF-α-induced insulin resistance in 3T3-L1 adipocytes [30].…”
mentioning
confidence: 99%
“…In addition to adipocytes, a previous study showed that APS can alleviate glucose toxicity by increasing liver glycogen synthesis and skeletal muscle glucose translocation in the T2DM rat model [ 28 ]. Moreover, APS attenuates insulin resistance in T2DM rats via regulation of liver microRNA-203a-3p [ 13 ]. Collectively, these data suggest that APS could be a potential insulin sensitizer for the treatment of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, APS alleviates diabetes and diabetes related complications. In a T2DM animal model, APS can effectively attenuate insulin resistance in both muscle and liver [ 12 , 13 ], but its regulatory effects and mechanisms on adipose tissue remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…AP-BBR was administered at a 1:1 mass ratio of AP: BBR. The above ratio was set up according to our previous studies on AP and BBR (Zitai et al, 2018;Zhu-jun et al, 2018). After successful establishment of the IR model, different concentrations of AP-BBR were added.…”
Section: Detection Of Hepg2 Cell Viability By Cck8mentioning
confidence: 99%